Acute coronary syndrome and chronic infection in the Cork coronary care case–control study. Issue 1 (16th December 2004) - Sheehan, J; Kearney, P M; Sullivan, S O; Mongan, C; Kelly, E; Perry, I J
Abstract : Objective: To examine the association between chronic infection and cumulative burden of infection and acute coronary syndrome. Design: The 5C (Cork coronary care case–control) study was a community based case–control study. Patients and controls underwent a standard physical examination and had blood samples taken for serological analysis for Helicobacter pylori (IgG), Chlamydia pneumoniae (IgA, IgM, and IgG), cytomegalovirus (IgG), and herpes simplex virus types 1 and 2 (IgG). Setting: Patients were recruited from four hospitals in Cork City and Mallow Town. Controls, individually matched on age and sex, were selected by incident density sampling from the same general practices as the referent case. Main outcome measures: Age and sex adjusted and fully adjusted odds ratios for acute coronary syndrome by seropositivity and by increasing number of infections. Results: Cases and controls did not differ significantly in seropositivity to C pneumoniae, cytomegalovirus, herpes simplex viruses, and H pylori . In unconditional logistic regression analysis adjusted for age, sex, waist to hip ratio, smoking, physical activity, alcohol consumption, and social class there was no evidence of an increasing risk for acute coronary syndrome with increasing burden of infection. Conclusions: The findings do not support an association between specific infectious agents and acute coronary syndrome and do not provide evidence of a burden of infection effect.